The Impact of the Original Local Government Revenue and Balanced Budget toward Capital Expenditure of the Government of Palangka Raya City - Rianti, Irma; ., Suwadi; Hukom, Alexandra (KnE Social Sciences, 2020)
The implementation of fiscal decentralization in improving services and necessity in various sectors including public sector has lead the Regional Government to allocate higher Capital Expenditure for the development of sectors that are considered beneficial in each region. The purpose of this study is that the researcher would like to investigate the impact of Original Local Government Revenue and Balanced Budget toward the Capital Expenditure of Palangka Raya City. The study was conducted in Palangka Raya City using a quantitative descriptive approach and multiple analysis for the data analysis. The results of the study indicates that part of Original Local Government Revenue does not have significant effect on Capital Expenditure. Meanwhile, part of the Balanced Budget has a significant effect on Capital Expenditure. Simultaneously, both of Original Local Government Revenue and Balanced Budget are able to influence local Capital Expenditure of the government of Palangka Raya City. Keywords: Original Local Government Revenue, Balanced Budget and Capital Expenditure